Lubrication effect of metal-on-metal in hip joint replacement [electronic resource] - Mohd. Syafiq Mohd. Suri, 1988- author (2014)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2014